Analysis of Correlation Interrelation of Bronchopulmonary Dysplasia in Late-Preterm Children - Maksudovna, Istamova Dilfuza (Journal of Science in Medicine and Life, 2025)
Bronchopulmonary dysplasia (BPD) is a special condition that develops in premature infants, which can become chronic, manifesting itself as a disease, since it is formed against the background of morphological changes in the lung tissue. As the child grows, clinical manifestations may reverse, but morphological changes may be persistent, contributing to the development of respiratory dysfunction that persists for a long time [8]. Known factors contributing to the development of this disease are gestational age (GA) and low birth weight. The development of respiratory distress syndrome (RDS) and long periods of artificial ventilation (ALV) complicate the course of the disease.